2017
DOI: 10.1089/acu.2017.1222
|View full text |Cite
|
Sign up to set email alerts
|

CranioSacral Therapy and Visceral Manipulation: A New Treatment Intervention for Concussion Recovery

Abstract: Background: Military service members and veterans face health issues related to traumatic brain injury (TBI), especially during combat, use of heavy equipment, and exposures to environmental hazards and explosives. There were 400,000 TBIs reported in deployed U.S. troops in 2012. Athletes are also subject to TBI. Studies have indicated that some manual therapies could be helpful for treating patients who have post-concussive syndrome.Objective: This case series report describes the effects of CranioSacral Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 22 publications
0
27
0
1
Order By: Relevance
“…OMT may be a beneficial adjunct for the care of concussed patients [5,[7][8][9][10]. Three case reports describe patients with isolated head injuries whose PCS improved after outpatient OMT [5,7,8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…OMT may be a beneficial adjunct for the care of concussed patients [5,[7][8][9][10]. Three case reports describe patients with isolated head injuries whose PCS improved after outpatient OMT [5,7,8].…”
Section: Discussionmentioning
confidence: 99%
“…A prospective case series describes an association between a focused, five-day craniosacral manipulation regimen and immediate and long-term PCS improvement [9]. A retrospective review demonstrated immediate improvements in the Standardized Concussion Assessment Tool 2 after one OMT session [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a form of noninvasive manual therapy that aims to correct any restrictions within the craniosacral system (CSS). The CSS is comprised of meninges, the bones attached to meninges, glia and CSF (Wetzler, Roland, Fryer-Dietz, & Dettmann-Ahern, 2017). The free and fluid movement between these structures are the focus behind the treatments therapeutic effects.…”
Section: Chiropractic and Osteopathic Manipulative Treatmentmentioning
confidence: 99%
“…18,19 Additionally, craniosacral therapy and visceral and neural manipulation have produced significant improvement in pain, cervical range of motion, and memory in former professional football players. 20 Recent research also demonstrates the safety of osteopathic cranial manipulative medicine in the treatment of patients with concussion. 19…”
Section: Osteopathic Structural Examinationmentioning
confidence: 99%